Anatomy-based human face reconstruction using multi-layer deformation - Zhang, Y. (2013)
13th International Conference in Central Europe on Computer Graphics, Visualization and Computer Vision 2005, WSCG'2005 - In Co-operation with EUROGRAPHICS, Full Papers